Self-assembly of trimetallic nitride template fullerenes on surfaces studied by STM - Leigh, D; Norenberg, C; Cattaneo, D; Owen, J; Porfyrakis, K; Bassi, A; Ardavan, A; Briggs, G (2007)
Trimetallic nitride template fullerenes have been deposited onto a variety of substrates in order to elucidate the substrate-fullerene interactions. We have investigated self-assembled island formation and molecular detail of Er3N@C-80 and SC3N@C-80 on Ag/Si(111), Au(111)/mica, Si(111), and Si(001) using variable temperature scanning tunnelling microscopy (STM). At room temperature, the fullerenes self-assemble into monolayer-high hexagonal close-packed islands on Ag-passivated Si(I 1 1) whereas annealing at elevated temperatures (250-300 degrees C) is necessary for the self-assembly of close-packed islands on An(111). Intra-molecular resolution of the fullerenes has been achieved at liquid nitrogen temperature on Ag/Si(111) and already at room temperature on Si(001), when the rotation of the fullerenes is frozen. Whereas the bonding between the fullerenes and Si surfaces is mainly covalent, it appears to be mainly vander-Waals on the other surfaces. (C) 2006 Elsevier B.V. All rights reserved.